Inland fishes of the Arabian Peninsula: Review and a revised checklist - Esmaeili, Hamid Reza; Hamidan, Neshat (Zootaxa, 2023)
The Arabian Peninsula comprises the seven countries of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates, and Yemen (including the Socotra archipelago), covering an area of more than 3 million km²). Although arid habitats cover most parts of the Arabian Peninsula, the region has several freshwater systems and comprises all or parts of four freshwater ecoregions basins that support a variety of inland aquatics including fishes. The current checklist provides all fish species in inland waters of the Arabian Peninsula including all recognized and named taxa, documenting recent changes and controversies in nomenclature, records, taxonomic status, occurrence, synonyms, common English name, range distribution, and conservation status based on several field surveys throughout the area and available articles. The confirmed inland ichthyodiversity of the Arabian Peninsula comprise 48 species belonging to 25 genera, 14 families, nine orders, and a class. Among these, 10 species (20.8%) are alien, and 21 species (52.3%) are considered endemic to the Arabian Peninsula. Favonigobius reichei is a new record for inland waters of the Arabian Peninsula. The most diverse order is Cypriniformes (19 species, 39.6%), followed by Cyprinodontiformes and Gobiiformes (eight species, 16.7% in each), Cichliformes (four species, 8.33%), Mugiliformes (three species, 6.25%), Anguilliformes and Siluriformes (two species, 4.17% in each), and Centrarchiformes and Gonorynchiformes (one species, 4.2% each). Saudi Arabia and Oman with 23 species (47.9% each) rank first in fish diversity (both native and exotic), followed by Yemen (15 species, 31.25%), UAE (seven species, 14.58%), Bahrain (two species, 4.17%), and Qatar and Kuwait (one species, 2.1% each). Of 21 endemic species of the Arabian Peninsula, six, six, and four species are restricted to the territories of Oman, Saudi Arabia and Yemen, respectively. No endemic fish have been reported from Bahrain, Kuwait, Qatar, and the United Arab Emirates. The list also includes two subterranean species belonging to the genus Garra. The provided data will be necessary to take action for effective conservation management strategies and policies.